(untitled) (Research, Society and Development, 2022)
This work addresses the challenges, methods and results of an extension project occcured during the Covid-19 pandemic. The project aimed to present Photoelectric Effect, Semiconductors and Atomic Spectra concepts, and low-cost experiments. All in a format of short courses. These contents are Modern Physics. Initially, the discussion and construction of themes was held. This first step was performed to facilitate the dissemination and promotion of scientific literacy for students. In order to achieve the objectives of dissemination and scientific literacy, students of the Degree in Physics at the Federal University of Southern and Southeastern Pará taught mini-courses, reaching an audience of 185 students. This audience consisted of students from four classes of two primary schools at Marabá city of the Pará state. In this work the results are reported.